Recognizing The Effect of Prior Knowledge in Economics and Cohesion Devices on Comprehending Business English Texts - Fachrukrozie Kodri (Fakultas Bahasa dan Sastra Universitas Kanjuruhan Malang, 2017)
Comprehending a text successfully is influenced by many factors. Texts will be easier to comprehend if learners are able to identify these essential factors. This study was aimed at recognizing the effect of using prior knowledge in economics and cohesion devices in comprehending business English texts. The research was conducted in Faculty of Economics and Business, Perbanas Institute – Jakarta. 75 students as respondents were selected using two stage cluster random sampling. Then three tests for all variables were given to the respondents. The data was used for analysis using SPSS multiple regression analysis. The result revealed that (1) prior knowledge in economics significantly influenced reading comprehension in business English text (2) the mastery of cohesion devices significantly influenced reading comprehension in business English texts (3) simultaneously both prior knowledge in economics and cohesion device mastery significantly influenced reading comprehension in business English texts.